Growth method of 8-inch hexagonal boron nitride thick film with high adhesive force

By using the vertical CVD method on an 8-inch 4H-SiC substrate to form a graphite intermediate layer, the problem of prone to cracking and curling at the micron level was successfully solved, and high adhesion and high-quality h-BN thick film growth was achieved, providing a feasible method for large-size device applications.

CN119913478AInactive Publication Date: 2025-05-02SUN YAT SEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510113672.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The traditional hexagonal boron nitride (h-BN) thick film growth method is prone to cracking and curling when the thickness of microns, making it difficult to achieve high adhesion and uniformity of the material.

Method used

A micrometer-level high-quality h-BN thick film was synthesized on an 8-inch silicon carbide (4H-SiC) single crystal substrate by vertical chemical vapor deposition (CVD) method. By forming pits and graphite intermediate layers on the substrate surface, internal stress is reduced and film adhesion and stability are improved.

Benefits of technology

The growth of a high adhesion 8-inch hexagonal boron nitride thick film is achieved, which avoids cracking and curling, ensures the integrity and quality of the film, and provides a feasible growth method for large-size micron-scale h-BN thick films, paving the way for the application of related devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913478A_ABST
    Figure CN119913478A_ABST
Patent Text Reader

Abstract

The invention discloses a method for growing a high-adhesion 8-inch hexagonal boron nitride thick film, which comprises the following steps of: synthesizing a micron-sized h-BN thick film on a 4H-SiC substrate by using chemical vapor deposition, placing the 4H-SiC substrate in a vertical CVD (Chemical Vapor Deposition) furnace, heating the 4H-SiC substrate under the air pressure of 10 <-3 > Pa at first, decomposing the surface of the substrate to form pits, evaporating Si atoms, and growing the thick film on the surface of the 4H-SiC substrate to form the 8-inch hexagonal boron nitride thick film. The remaining C atoms are crystallized on the surface of the substrate to form a graphite buffer layer, and the surfaces of the pits are covered with the graphite buffer layer; and on the basis, reaction gas is introduced, and the micron-sized h-BN thick film is formed on the surface of the graphite buffer layer. The surface of the 4H-SiC is decomposed to form the pits and the interlayer of the layered graphite, then the h-BN film is deposited on the basis of the pits and the interlayer of the layered graphite, and due to the growth mechanism, the micron-sized h-BN thick film does not curl or crack during growth. Therefore, the method disclosed by the invention possibly becomes a promising method for preparing the large-size high-quality micron-sized h-BN thick film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of boron nitride preparation, and in particular to a method for growing an 8-inch hexagonal boron nitride thick film with high adhesion. Background Art

[0002] Hexagonal boron nitride (h-BN) is a common boron-containing material used in semiconductor neutron detectors. 10 B has a large neutron capture cross section (3840 barns) and a high natural abundance (19.8%). In addition, h-BN exhibits excellent properties such as high breakdown field strength, high chemical stability, and radiation resistance. Therefore, as a semiconductor neutron detection material, h-BN has significant advantages and is expected to replace traditional 3 He gas neutron detector. Neutrons react with h-BN to produce alpha particles and lithium nuclei with sufficient kinetic energy to generate electron-hole pairs in the h-BN material.

[0003] Large-area uniform growth of micron-scale h-BN thick films is a prerequisite for the above applications. Traditional single crystal growth and mechanical exfoliation methods are difficult to control the thickness and lateral size of two-dimensional materials, and their morphology cannot meet the requirements of practical applications. Therefore, large-area growth of h-BN is urgently needed. Chemical vapor deposition (CVD) is a widely used two-dimensional material synthesis tool with fast growth rate, free precursor selection, and allows wafer-level growth of two-dimensional materials. CVD is widely used in the growth of single-layer or multi-layer h-BN films on metal substrates such as nickel, copper, platinum, iridium, and gold, as well as dielectric substrates such as sapphire and quartz. However, when the films reach micron-scale thickness, they are very prone to cracking and curling. This problem stems from the internal stress caused by the difference in thermal expansion coefficients of the materials, lattice mismatch, or temperature changes during the deposition process. Summary of the invention

[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a method for growing an 8-inch hexagonal boron nitride thick film with high adhesion, and constructing a serrated intermediate layer can reduce the probability of cracking and curling problems. The present invention uses a vertical CVD furnace to synthesize a micron-scale high-quality h-BN thick film on an 8-inch silicon carbide (4H-SiC) single crystal substrate. The good quality and uniformity of the thick film are demonstrated by a series of characterizations such as X-ray photoelectron spectroscopy, infrared, and Raman. The growth mechanism of the micron-scale film was analyzed in detail by transmission electron microscopy. The results show that in the early stage of growth, the SiC surface is slightly decomposed to form pits and a graphite intermediate layer, which allows the later grown micron-scale h-BN thick film to remain intact.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect of the present invention, a method for growing an 8-inch hexagonal boron nitride thick film with high adhesion is provided, wherein a micron-sized hexagonal boron nitride thick film is synthesized on a 4H-SiC substrate using chemical vapor deposition, comprising the following steps:

[0007] Step S1, placing the 4H-SiC substrate into a vertical chemical vapor deposition furnace, and evacuating the furnace to 10-3Pa;

[0008] Step S2, heating the furnace body to the reaction temperature and then keeping it warm, the substrate surface is decomposed to form pits, Si atoms evaporate, and the remaining C atoms crystallize into a graphite buffer layer on the substrate surface, and the surface of the pit is covered by the graphite buffer layer; then N2 is used as a carrier gas and a protective gas, and two raw material gases NH3 and BCl3, or NH3 and BF3 are introduced into the furnace body, so that the two gases are mixed and reacted in the middle of the deposition chamber, so that the grown hexagonal boron nitride is uniformly deposited on the substrate; after ventilation, the temperature is maintained at the reaction temperature, and the temperature is kept for a period of time;

[0009] Step S3, turn off the power, and let the hexagonal boron nitride film / 4H-SiC cool down in the furnace and then be taken out of the furnace at room temperature, and then the hexagonal boron nitride film is peeled off from the 4H-SiC substrate to obtain a hexagonal boron nitride thick film.

[0010] Furthermore, in step S2, the furnace body is heated to a reaction temperature of 1800-1900° C. by using a lateral resistor and then kept warm, and two raw material gases NH 3 and BCl 3 or NH 3 and BF 3 enter the deposition chamber from the bottom.

[0011] Furthermore, in step S2, the volume ratio of the two raw material gases NH3 and BCl3, or NH3 and BF3 is 1.4-1.5:1.

[0012] Furthermore, in the step S2, the temperature of the furnace body is maintained at the reaction temperature of 1800-1900° C. after ventilation, and the growth is kept warm for 3.8-4.2 hours.

[0013] Furthermore, the vertical chemical vapor deposition furnace is provided with a graphite cylinder with a furnace cavity, a heater, a thermal insulation layer and a shell from the inside to the outside, the heater is arranged on the side of the graphite cylinder, the lower and upper parts of the graphite cylinder are respectively provided with an air inlet and an air outlet, a clamp is provided in the middle of the graphite cylinder, and a 4H-SiC substrate is clamped at the lower part of the clamp.

[0014] The second aspect of the present invention provides an 8-inch hexagonal boron nitride thick film with high adhesion prepared by the above hexagonal boron nitride thick film growth method.

[0015] Furthermore, the hexagonal boron nitride thick film has a layered structure, the main crystal plane is the (002) plane, and there are also (100) and (004) planes.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] A complete, high-quality, micron-sized h-BN thick film was synthesized on an 8-inch 4H-SiC single crystal substrate using a vertical chemical vapor deposition furnace. The 4H-SiC surface was slightly decomposed to form pits and an intermediate layer of layered graphite, on which the h-BN thick film was deposited. This growth mechanism prevented the growth of the micron-sized h-BN thick film from curling and cracking. Therefore, the feasibility of growing micron-sized h-BN thick films on 4H-SiC single crystals has been verified, and it is expected to become one of the growth methods for large-sized micron-sized h-BN thick films, paving the way for further development of related device applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the growth of the hexagonal boron nitride thick film and a physical picture of the thick film in Example 1 of the present invention;

[0019] Figure 2 This is a physical picture of growing a micron-scale h-BN thick film on a sapphire single crystal substrate in Example 2 of the present invention;

[0020] Figure 3 It is a schematic structural diagram of a vertical chemical vapor deposition furnace in Example 3 of the present invention;

[0021] Figure 4 The optical micrograph, XRD spectrum, FTIR spectrum and XPS characterization result diagram of the micron-sized h-BN thick film in Example 4 of the present invention are shown;

[0022] Figure 5 This is a graph showing the Raman spectrum characterization test results of the h-BN thick film after peeling in Example 5 of the present invention;

[0023] Figure 6 This is a comparison photo of a standard 4H-SiC substrate sheet and a 4H-SiC substrate sheet after peeling in Example 6 of the present invention;

[0024] Figure 7 This is a cross-sectional TEM characterization test result diagram of the 4H-SiC substrate after peeling in Example 6 of the present invention;

[0025] Figure 8 This is a cross-sectional TEM characterization test result diagram of the h-BN thick film after peeling in Example 6 of the present invention.

[0026] In the figure:

[0027] 1-graphite cylinder; 11-air inlet; 12-air outlet; 13-clamp; 14-substrate; 2-heater. DETAILED DESCRIPTION

[0028] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0029] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0030] Example 1: Method for growing 8-inch hexagonal boron nitride thick film with high adhesion

[0031] This embodiment is used to provide a method for growing an 8-inch hexagonal boron nitride thick film with high adhesion according to the present invention. Figure 1 The growth diagram of the hexagonal boron nitride thick film and the actual image of the thick film of the present invention are shown in FIG. Figure 1 a is a schematic diagram of the growth mechanism of micron-scale hexagonal boron nitride thick film grown on 4H-SiC substrate. Figure 1 b and Figure 1 c are the actual pictures of micron-level 8-inch and 6-inch hexagonal boron nitride thick films synthesized by the present invention, such as Figure 1 As shown in a, the method for growing a high-adhesion hexagonal boron nitride thick film of the present invention comprises the following steps:

[0032] Step S1: Place 8-inch and 6-inch 4H-SiC substrates into a vertical chemical vapor deposition furnace, and evacuate the furnace to 10 -3 Pa;

[0033] Step S2, then use resistance heating to 1800-1900°C for heat preservation, use N2 as carrier gas and protective gas, and introduce two raw material gases NH3 and BCl3 (or NH3 and BF3) into the furnace body at a volume ratio of 1.45:1; wherein, the two raw material gases NH3 and BCl3 (or NH3 and BF3) enter the deposition chamber from the bottom, so that the two gases are mixed and reacted in the middle of the deposition chamber, so that the grown hexagonal boron nitride is uniformly deposited on the substrate; after ventilation, the furnace body temperature is maintained at 1800-1900°C, and the heat preservation growth is carried out for 4 hours;

[0034] Step S3, then turn off the power, cool the hexagonal boron nitride / 4H-SiC in the furnace and take it out of the furnace at room temperature, peel the hexagonal boron nitride film from the 4H-SiC substrate, and obtain the hexagonal boron nitride thick film of the present invention.

[0035] In this embodiment, in the initial stage of hexagonal boron nitride film growth, the 4H-SiC substrate is slightly decomposed at high temperature, Si atoms form steam, and the remaining C atoms form a layered graphite middle layer on the surface of the 4H-SiC substrate, and small pits are formed on the surface, which form nucleation sites for the subsequent hexagonal boron nitride film. On this basis, the introduction of raw gas NH3 and BCl3 (or NH3 and BF3) generates a hexagonal boron nitride film on the graphite surface. Since graphite and hexagonal boron nitride have the same crystal structure and nearly the same lattice constant, hexagonal boron nitride is easier to grow on graphite.

[0036] Figure 1 b and Figure 1 c are the micron-scale hexagonal boron nitride thick films just grown on 8-inch and 6-inch 4H-SiC substrates, with a thickness of about 40μm.

[0037] Example 2: Using a sapphire single crystal substrate to replace a 4H-SiC substrate to grow a micron-scale h-BN thick film

[0038] This embodiment is used to provide a comparative example of the method for growing a hexagonal boron nitride thick film different from that described in Embodiment 1 of the present invention. In this embodiment, a sapphire single crystal substrate is used to replace the 4H-SiC substrate in Embodiment 1 to grow a micron-scale h-BN thick film. Figure 2 a and Figure 2 b are actual pictures of hexagonal boron nitride thick films with thickness of 100μm and 20μm grown on sapphire single crystal substrate.

[0039] like Figure 2 a and Figure 2 As shown in b, the 100μm film cracked, and the 20μm film cracked and curled. Sapphire is one of the commonly used substrates for h-BN film growth. The experimental results show that the h-BN thick film will crack and detach from the substrate ( Figure 2 a). Even when controlled to grow to a thinner thickness (~20 μm), the h-BN film still cracks and rolls into strips ( Figure 2 b). In addition, the sapphire substrate is still very smooth after growth. There are two possible reasons for the failure: First, compared with 4H-SiC, the thermal expansion coefficients of sapphire and h-BN are too different, resulting in cracking of the grown film layer. Second, there is no intermediate layer as a connection, and the h-BN film is easily separated from the substrate. In comparison, when growing a thick h-BN film on a 4H-SiC substrate, the 4H-SiC surface decomposes to form pits and a graphite intermediate layer, making the h-BN film less likely to crack and curl. This result also indirectly proves the feasibility of growing h-BN on a 4H-SiC substrate.

[0040] Example 3: Vertical Chemical Vapor Deposition Furnace Structure for Hexagonal Boron Nitride Thick Film Growth

[0041] This embodiment is used to provide a specific structure of a vertical chemical vapor deposition furnace in the hexagonal boron nitride thick film growth method described in Example 1 of the present invention. Figure 3 It is a schematic structural diagram of the vertical chemical vapor deposition furnace of the present invention.

[0042] As shown in the figure, the vertical chemical vapor deposition furnace is provided with a graphite tube 1 with a furnace cavity, a heater 2, a thermal insulation layer and a shell from the inside to the outside. The heater 2 is arranged on the side of the graphite tube 1. The lower and upper parts of the graphite tube 1 are respectively provided with an air inlet 11 and an air outlet 12. A clamp 13 is provided in the middle of the graphite tube 1, and a 4H-SiC substrate 14 is clamped at the lower part of the clamp 13. In this embodiment, the vertical chemical vapor deposition furnace adopts resistance lateral heating, and the raw material gas enters the deposition furnace from the bottom. Since the traditional CVD system usually adopts a horizontal tube furnace with a limited diameter, the synthesis of h-BN films of larger sizes is severely restricted. The present invention adopts an improved vertical deposition furnace to effectively suppress the short-term heating of the deposition furnace caused by various reasons. It has a simple structure and good thermal insulation effect. It can accommodate substrates of 6 inches, 8 inches or even larger areas.

[0043] In this embodiment, the precursors of boron and nitrogen are NH3 and BCl3, and the carrier gas is N2. At a high temperature of 1800-1900°C, the two react to form BN and HCl (BCl3+NH3→BN+3HCl), solid h-BN is deposited on the 4H-SiC substrate, and gaseous HCl is discharged as tail gas. Due to the high temperature growth conditions of h-BN, the high temperature resistance of the substrate is required to be high.

[0044] Example 4: X-ray diffraction performance characterization test of micron-scale 6-inch h-BN thick film

[0045] The micron-scale 6-inch h-BN thick film was peeled off from the 4H-SiC substrate, and the performance characterization test of the h-BN thick film sample after peeling was carried out. The X-ray diffraction (XRD) spectrum was measured using a Panalytical X'Pert Pro X-ray diffractometer (with Cu-Kαradiation); the Fourier transform infrared (FTIR) spectrum test was conducted using a SHIMADZU IRAffinity-IS Fourier transform infrared spectrometer, using a gold mirror as a reflective background; the X-ray photoelectron spectroscopy (XPS) was measured using a ThermoESCALAB 250Xi multifunctional imaging electron spectrometer.

[0046] Figure 4 The optical micrograph, XRD spectrum, FTIR spectrum and XPS characterization result diagram of the micron-scale 6-inch h-BN thick film of this embodiment are shown in FIG. Figure 4 a is an optical micrograph of the h-BN thick film after magnification. Figure 4b is the XRD spectrum of h-BN thick film, showing the (002) main crystal plane, and the inset is a schematic diagram of the layered atomic arrangement of h-BN. Figure 4 c is the FTIR spectrum. Due to the interference effect of the film, the spectrum has interference fringes. Figure 4 d is B 1s and N 1s XPS.

[0047] Depend on Figure 4 It can be seen that the grown 6-inch h-BN thick film exhibits good crystal quality and crystal plane orientation. Figure 4 a is an optical micrograph of the h-BN thick film, from which it can be seen that the film surface is uniform and smooth without obvious grain accumulation. Figure 4 b is the XRD spectrum, which shows that h-BN has a relatively single c-plane orientation. h-BN atoms interact with each other along the c-axis through atomic van der Waals forces, and have typical layered material properties, such as Figure 4 bAs shown in illustration. Figure 4 c is the FTIR spectrum. Due to the interference effect of the film, interference fringes appear in the spectrum. However, the characteristic signals of the spectrum are still obvious, among which 799cm -1 and 1415cm -1 The signals at 1560 cm-1 come from the out-of-plane BNB bending vibration and in-plane BN stretching vibration of h-BN. -1 There is a small peak at , which may come from the double phonon vibration peak of h-BN, or the C=N vibration caused by carbon impurities. Further, XPS was measured and the characteristic peaks were fitted and analyzed, such as Figure 4 d. B 1s The peak at 190.6 eV is attributed to the BN bond in h-BN. 1s From the XPS, it can be clearly seen that the spectrum has a tailing phenomenon on the high energy side. The double peaks of 398.1eV and 398.8eV were obtained by peak fitting, of which 398.1eV comes from the BN bond of h-BN, while the peak of 398.8eV with lower intensity and on the high energy side of the BN peak may be the CN bond.

[0048] Example 5: Raman spectroscopy characterization test of h-BN thick film after peeling

[0049] The micron-scale h-BN thick film was peeled off from the 4H-SiC substrate, and the h-BN thick film sample was tested for uniformity using a Raman spectrometer. The Raman spectrum was collected using a Horiba LabRam HR Evolution microscope confocal Raman system excited by a 532nm laser. The Raman scattered light was collected in backscattering mode and split using a 1800 lines / mm grating, with a spectral resolution of 0.65 cm -1The test range of Raman Mapping is 50×50μm, and the step length is 5μm. The fluorescence background signal of Raman spectrum is subtracted, and then the E 2g The characteristic peaks were fitted with Lorentz fitting to obtain the half-width data. The test results are as follows Figure 5 As shown. Among them, Figure 5 a is the Raman spectrum of a 6-inch h-BN thick film at the micron level; Figure 5 b shows the 14 marking positions of Raman Mapping test on a 6-inch h-BN thick film; Figure 5 c is the Raman half-width mapping diagram of 14 areas on the film.

[0050] like Figure 5 As shown in Figure 1, a typical Raman spectrum of a 6-inch h-BN thick film at the micron level is shown. Although the spectrum shows a low fluorescence background, it shows a good Raman peak shape, which is the characteristic vibration mode E of h-BN. 2g . E 2g The Raman peak is at 1368.5 cm -1 , half height width is 26.0cm -1 ( Figure 5 a). To further verify the quality uniformity of the grown film, Raman mapping of 14 regions on the film was measured, which showed that E 2g The half-width of the mode ( Figure 5 b) The half-height widths of the 14 regions are similar, ranging from 24.5 to 27.0 cm -1 The range of fluctuations indicates that the film has high uniformity ( Figure 5 c).

[0051] Example 6: Cross-sectional TEM characterization test of 4H-SiC substrate and h-BN thick film after peeling

[0052] The micron-sized h-BN thick film is peeled off from the 4H-SiC substrate. Taking the grown 2-inch h-BN thick film as an example, Figure 6 For standard 4H-SiC substrate ( Figure 6 a) and 4H-SiC substrate after growth and peeling ( Figure 6 b) Compare with the actual picture.

[0053] The stripped substrate was subjected to a cross-sectional transmission electron microscope (TEM) characterization test. The sample preparation used the ion gun of a FEI Helios 5UX focused dual-number scanning electron microscope, and the TEM test used a FEI Talos F200X transmission electron microscope. The results are shown in Figure 2. Figure 7 As shown. Among them, Figure 7 a is a low magnification cross-sectional TEM image, Figure 7 b is a high-resolution cross-sectional TEM image. The test area is the yellow circle area in (a). Figure 7 c is the cross-sectional TEM energy spectrum (EDS) mapping image, and the test area is the blue circle area in (a). Figure 7 d is a typical high-resolution cross-sectional TEM image. The silicon carbide substrate is decomposed at high temperature, and layered graphite is formed at the interface. Figure 7 e is the 266 nm ultraviolet laser Raman spectrum of the substrate after peeling.

[0054] After the micron-scale h-BN thick film is peeled off from the 4H-SiC substrate, the substrate surface shows a dark black color different from its original yellow-green color ( Figure 6 ), indicating that there are other substances on the substrate surface besides the substrate material. Therefore, the peeled substrate was subjected to cross-sectional transmission electron microscopy (TEM) analysis. The low-magnification TEM image showed that the grown silicon carbide substrate was uneven and had obvious pits due to corrosion ( Figure 7 a). The high-resolution TEM image of the interface at the pit shows that a multilayer film has grown on the interface at the pit ( Figure 7 b). Furthermore, through the energy spectrum (EDS) surface scanning test, it was found that the film grown at the 4H-SiC interface contained less N elements and more C elements, indicating that it was not an h-BN film ( Figure 7 c). Therefore, a typical high-resolution interface TEM image was selected for analysis, and it can be clearly seen that the SiC substrate is corroded, and the interplanar spacing of the film at the interface in the c direction is 0.35nm. Combined with the results of the EDS surface scan, it is inferred that the film is layered graphite, indicating that the SiC substrate is decomposed at high temperature and layered graphite is formed at the interface ( Figure 7 d). Finally, the 266nm ultraviolet laser Raman spectrum of the peeled substrate was tested. -1 The main peak is the G mode of graphite, 776.7cm -1 The small peak at is the E2(TO) mode of 4H-SiC ( Figure 7 e), which also confirms that the film at the 4H-SiC interface is graphite.

[0055] Furthermore, the cross-sectional TEM test was also performed on the peeled h-BN thick film. The results are as follows: Figure 8 As shown, Figure 8 a is a low magnification TEM image of the h-BN film. Figure 8 b is the selected electron diffraction spectrum, Figure 8 c is the high-resolution TEM image of h-BN thick film.

[0056] Figure 8 In a, we can see that the h-BN film has layered characteristics, but the layer structure is not unidirectional. Therefore, the grown h-BN thick film is polycrystalline. Figure 8The electron diffraction spectrum of b shows that the main crystal plane of the h-BN film is the (002) plane, with a small amount of (100) and (004) planes, which is consistent with the XRD test results ( Figure 5 b), indicating that the grown h-BN thick film still has a relatively single orientation. Figure 8 In c, the layered structure of h-BN can be clearly observed, and the calculated interplanar spacing is 0.34 nm, representing the (002) plane.

[0057] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for growing a high-adhesion 8-inch hexagonal boron nitride thick film, characterized in that: The method uses chemical vapor deposition to synthesize a micrometer-sized hexagonal boron nitride thick film on a 4H-SiC substrate, including the following steps: Step S1: Place the 4H-SiC substrate into a vertical chemical vapor deposition furnace, and evacuate the furnace to 10 -3 Pa; Step S2, heating the furnace body to the reaction temperature and then keeping it warm, the substrate surface is decomposed to form pits, Si atoms evaporate, and the remaining C atoms crystallize into a graphite buffer layer on the substrate surface, and the surface of the pit is covered by the graphite buffer layer; then N2 is used as a carrier gas and a protective gas, and two raw material gases NH3 and BCl3, or NH3 and BF3 are introduced into the furnace body, so that the two gases are mixed and reacted in the middle of the deposition chamber, so that the grown hexagonal boron nitride is uniformly deposited on the substrate; after ventilation, the furnace body temperature is maintained at the reaction temperature, and the growth is kept warm for a period of time; Step S3, turn off the power, and let the hexagonal boron nitride film / 4H-SiC cool down in the furnace and then be taken out of the furnace at room temperature, and then the hexagonal boron nitride film is peeled off from the 4H-SiC substrate to obtain a hexagonal boron nitride thick film.

2. The method for growing an 8-inch hexagonal boron nitride thick film with high adhesion according to claim 1, characterized in that: In step S2, the furnace body is heated to a reaction temperature of 1800-1900° C. by using a lateral resistor and then kept warm, and two raw material gases NH 3 and BCl 3 or NH 3 and BF 3 enter the deposition chamber from the bottom.

3. The method for growing an 8-inch hexagonal boron nitride thick film with high adhesion according to claim 1, characterized in that: In step S2, the volume ratio of the two raw material gases NH3 and BCl3, or NH3 and BF3 is 1.4-1.5:

1.

4. The method for growing an 8-inch hexagonal boron nitride thick film with high adhesion according to claim 1, characterized in that: In the step S2, the temperature of the furnace body is maintained at the reaction temperature of 1800-1900° C. after ventilation, and the growth is kept at this temperature for 3.8-4.2 hours.

5. The method for growing an 8-inch hexagonal boron nitride thick film with high adhesion according to claim 1, characterized in that: The vertical chemical vapor deposition furnace is provided with a graphite cylinder (1) having a furnace cavity, a heater (2), a thermal insulation layer and an outer shell from the inside to the outside, the heater (2) is arranged on the side of the graphite cylinder (1), the lower part and the upper part of the graphite cylinder (1) are respectively provided with an air inlet (11) and an air outlet (12), the middle part of the graphite cylinder (1) is provided with a clamp (13), and the lower part of the clamp (13) clamps a 4H-SiC substrate (14).

6. High adhesion 8-inch hexagonal boron nitride thick film, characterized by: The film is prepared by the high-adhesion 8-inch hexagonal boron nitride thick film growth method described in any one of claims 1 to 5.

7. The 8-inch hexagonal boron nitride thick film with high adhesion according to claim 6, characterized in that: The hexagonal boron nitride thick film is a layered structure, the main crystal plane is the (002) plane, and there are (100) and (004) planes at the same time.

Citation Information

Patent Citations

  • Direct formation of hexagonal boron nitride on silicon based dielectrics

    CN109791876A

  • Hexagonal boron nitride film growth method and hexagonal boron nitride film

    CN112086343A

  • High-quality hexagonal boron nitride film growing by taking diamond as substrate and preparation method of high-quality hexagonal boron nitride film

    CN113053732A

  • Semiconductor lamination, and manufacturing method thereof

    JP2007329354A